INCREASED ATTENTION TO COTTON FARMING IN TURKESTAN DURING RUSSIAN RULE - Мусаев Н. У (TARIXIY TADQIQOTLAR, 2025)
The strengthening of the positions of the United States and Russia in the Persian Gulf, the strengthening of Britain’s influence in the Persian Gulf, the strengthening of the US position in the Persian Gulf, the strengthening of the US position in the Persian Gulf, the strengthening of the US position in the Persian Gulf. Russian capitalists established large farms in Turkestan that specialized in cotton.